4.4 V supercapacitors based on super-stable mesoporous carbon sheet made of edge-free graphene walls. Issue 5 (6th February 2019) - Nomura, Keita; Nishihara, Hirotomo; Kobayashi, Naoya; Asada, Toshihiro; Kyotani, Takashi
Abstract : Super-stable mesoporous carbon sheet made of edge-free graphene walls enabled the assembly of symmetric supercapacitors with excellent stability under 3.5 V@60 °C and 4.4 V@25 °C conditions, even with a conventional electrolyte. Abstract : The application of supercapacitors for objectives such as automobiles requires high voltage and high temperature operation, therefore development of new electrode materials that have sufficient stability under such harsh conditions is crucial. In this work, we report the development of seamless mesoporous carbon sheet consisting of continuous graphene walls, which exhibits extraordinarily high stability under high voltage and high temperature conditions. The sheet contains very few carbon edge sites (only 4% of the number present in conventional activated carbons) despite its high specific surface area (1500 m 2 g −1 ), and it is possible to use it to assemble symmetric supercapacitors with excellent stability under 3.5 V@60 °C and 4.4 V@25 °C conditions, even using a conventional electrolyte (1 M Et3 MeNBF4 /propylene carbonate). Moreover, high-voltage operation at 4.4 V results in a 2.7 times higher energy density compared to that achieved using conventional activated carbons.